One missed call - Johnson, Broderick; Kosove, Andrew A.; Kroopf, Scott; Tugend, Jennie Lew.; Weissman, Lauren C.; Klavan, Andrew; Valette, Eric.; Sossamon, Shannyn, 1978-; Burns, Edward, 1968-; Talancon, Ana Claudia; Wise, Ray, 1947-; Skye, Azura, 1981-; et al. (Burbank, CA Distributed by Warner Home Video, 2008)
Beth Raymond is a college student who begins losing all her friends after one of her classmates is found dead. She doesn't understand why. All she knows is that each of her friends received a voicemail on their cell phones, one that told them when they would die and what they would say at the moment of their death. Each time a person gets a call, his or her phone plays a quiet music box lullaby instead of its normal ring tone. After ther person hears the message, they begin to see disturbing things. As soon as they die, they cough up a piece of hard candy, after which their cell phones dial another number, notifying the next person to die on the list. Beth eventually gets the call. With the help of Officer Jack Andrews, Beth hopes to solve this mystery before her time runs out.
Based on the novel 'Chakushin ari' by Yasushi Akimoto and the 2003 screenplay by Miwako Daira.
Director of photography, Glen MacPherson ; editor, Steve Mirkovich ; music, Reinhold Heil, Johnny Klimek ; costume designer, Sandra Hernandez ; production designer, Laurence Bennett.
Shannyn Sossamon, Edward Burns, Ana Claudia Talancon, Ray Wise, Azura Skye.
MPAA rating: PG-13; for intense sequences of violence and terror, frightening images, some sexual material and thematic elements.
Canadian Home Video rating: 14A; frightening scenes; violence.
DVD, region 1, full screen (1.33:1) and widescreen (matted, enhanced) presentations; Dolby Digital 5.1 surround.
Keywords: College students -- United States -- Drama; Cell phones -- United States -- Drama; Ring tones -- Drama; Violent deaths -- United States -- Drama; Criminal investigation -- United States -- Drama; United States; Thrillers (Motion pictures, television, etc.); DVD-Video discs; Thrillers (Television programs); Drama; Feature films; Fiction films; Film remakes; Horror films; Suspense films; Video recordings for the hearing impaired